Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1088/1748-6041/11/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

In vivoassessment of a new multifunctional coating architecture for improved Mg alloy biocompatibility

Abstract: Magnesium alloys are regarded as potential biodegradable load-bearing biomaterials for orthopedic applications due to their physico-chemical and biomechanical properties. However, their clinical applicability is restricted by their high degradation rate, which limits the physiological reconstruction of the neighbouring tissues. In this work, a multifunctional coating architecture was developed on an AZ31 alloy by conjoining an anodization process with the deposition of a polymeric-based layer consisting of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 74 publications
(85 reference statements)
4
8
0
Order By: Relevance
“…Yoshizawa et al found enhanced PGC-1α expression in the presence of Mg 2+ in bone marrow stromal cells 40 . An in vivo experiment also confirmed the positive effect of Mg 2+ on the expression of PGC-1α 41 . Consequently, our existing data demonstrate the specific molecular mechanism regulated by intracellular Mg 2+ .…”
Section: Discussionsupporting
confidence: 57%
“…Yoshizawa et al found enhanced PGC-1α expression in the presence of Mg 2+ in bone marrow stromal cells 40 . An in vivo experiment also confirmed the positive effect of Mg 2+ on the expression of PGC-1α 41 . Consequently, our existing data demonstrate the specific molecular mechanism regulated by intracellular Mg 2+ .…”
Section: Discussionsupporting
confidence: 57%
“…Closer examination of inflammatory relationships (e.g., the involvement of different cell types and the alignment of macrophages) could also be of interest for further development of this material class [19]. Finally, the direct comparison or amplification of other surface modifications such as duplex-(MgF 2 /PCL) [50], nanocomposite- [73] and composite-coatings [51,74] as well as the extension of other magnesium alloys [47][48][49][50][51][75][76][77][78][79][80][81] should be investigated and might promise new results in the future. Overall, especially in comparison with other studies, there is further need for simplification and standardization of in vitro and in vivo studies of magnesium-based materials.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also identified that 193 (7.9%) of articles used CAM method to test inorganic compounds and 89 (3,9%) used it to test nanoparticles (Fig 3). The main goal of these articles was to evaluate if the tested compound could be used in implants (GOMES et al, 2016); or to verify if the sample tested was toxic (AHMAD et al, 2016); or if the compound could promote tumor angiogenesis (KAMBLE et al, 2016). Then, our data indicate that CAM assay is widely used, but seems to be more often seen in articles aiming to investigate biological questions linked to cancer research.…”
Section: Applications Of Cam Assaymentioning
confidence: 97%